2015
DOI: 10.1111/corg.12144
|View full text |Cite
|
Sign up to set email alerts
|

Business Groups and Corporate Governance: Review, Synthesis, and Extension

Abstract: Manuscript Type: ReviewResearch Question/Issue: This article addresses the diverse and fragmented literature about the corporate governance of business groups. We collected scholarly work on the subject, proposed a conceptualization of the main research questions they addressed, classified them according to their research themes, and identified future research directions. Research Findings/Insights: Academic research on corporate governance in business groups has been increasing but is still a developing field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 171 publications
(189 reference statements)
1
49
0
Order By: Relevance
“…Their article offers an excellent summary of the current literature, concluding by offering future research directions. Colli and Colpan (2016) engage in an extensive review of a massive yet "siloed" (or segmented) literature on business groups. Their goal is to dissect from this large body of research what have we learned on how business groups design their corporate governance.…”
Section: Synopses Of Articles Included In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Their article offers an excellent summary of the current literature, concluding by offering future research directions. Colli and Colpan (2016) engage in an extensive review of a massive yet "siloed" (or segmented) literature on business groups. Their goal is to dissect from this large body of research what have we learned on how business groups design their corporate governance.…”
Section: Synopses Of Articles Included In This Issuementioning
confidence: 99%
“…For instance, a recent stream of research has addressed corporate governance in emerging economies such as China and India, whose institutional environments are less developed or quite different from those of advanced economies (Chen, Liu, & Lin, 2015;Huyghebaert & Wang, 2012;Lattemann, Fetscherin, Alon, Li, & Schneider, 2009;Li, 2013;Nagar & Sen, 2016;Singh & Gaur, 2009;Zhang, Chen, & Feng, 2014;Zhang, Gao, Guan, & Jiang, 2014). It is claimed that business groups are an organizational form that can overcome market imperfections prevalent in emerging economies (Colpan, Hikino, & Lincoln, 2010; They exhibit unique governance challenges as well as attributes to overcome broader strategic issues such as institutional voids or competitiveness, as summarized by Colli and Colpan's (2016) article in this special issue. In addition, institutional elements in a country tend to complement each other, giving rise to the varieties of capitalism (Hall & Soskice, 2002), and national business systems (Whitley, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We have incorporated the hierarchical relationship between a prior adopter and the focal firm, thereby suggesting that board interlocks are sometimes embedded in interfirm ties and reflect underlying power relationships. Board interlocks are prevalent in many institutional contexts, but such ties are often used as an interfirm control mechanism within a business group, especially in emerging economies (Boyd & Hoskisson, ; Colli & Colpan, ) but also in some developed economies (Colpan & Hikino, ; Lincoln et al, ). This study brings hierarchical power relationships into board interlock research.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that executives sent by those corporate owners are able to yield power based not only on equity stakes but sometimes also on the resource (Casiaro & Piscorski, 2005) that the core or higher status institution can provide to the focal firms (Zona et al, 2018). This practice is similar to how core firms in a business group control other firms in other institutional contexts such as South Korea, Turkey, and some Western countries (Boyd & Hoskisson, 2010;Colli & Colpan, 2016;Colpan & Hikino, 2018). We often observe similar board ties created by executive transfers in the context of equity strategic alliances, too.…”
Section: Boards Of Directors In Japanmentioning
confidence: 99%
“…A price war is likely to start among the partners within the collusive if they find exceptional earning. Similarly, Colli and Colpan (2016) identified that exceptional earnings might result in decreased overall earnings. The collusive activities are facilitated by successful collusive that is possessed by the concentrated industries (Bolotova, Connor, & Miller, 2008).…”
Section: Relevant Scholarshipmentioning
confidence: 99%